PENGARUH REPUTASI, KEPUASAN DALAM DISTRIBUSI ZAKAT, DAN KUALITAS LAYANAN TERHADAP KEPERCAYAAN MUZAKKI PADA BAITUL MAL KOTA BANDA ACEH - Nurul Husna; Farid Farid (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
Abstract: This study aims to measure the effect of Reputation, Satisfaction of Zakat Distribution, and Service Quality on Muzakki's Trust at Baitul Mal Banda Aceh. The sample used in this study was muzakki who paid zakat at Baitul Mal Banda Aceh, which amounted to 120 respondents. Data collection equipment used in this study is a questionnaire. The sampling technique used is Nonprobability Sampling, this technique is used because the profitability of elements in the population to be selected as samples is unknown. Multiple linear regression is used as an analytical method to determine the effect of all the variables involved.The results sh owed that the independent variable Reputation, Satisfaction of Zakat Distribution, and Service Quality had a positive and significant effect (sig 0.05) on the Muzakki’s Trust at Baitul Mal Banda Aceh with a regression coefficient of Reputation (X1) 0.354, Satisfaction of Zakat Distribution (X2) 0.393, Service Quality (X3) 0.494. Simultaneous Reputation variables, Satisfaction of Zakat Distribution, and Service Quality have a significant effect on Muzakki’s Trust